TEACHERS’ PERCEPTION ON THE USE OF ALTERNATIVE ASSESSMENT IN INTERNATIONAL PRIMARY SCHOOL: BENEFITS AND OBSTACLES - Purnamasari, Rike; Anam, Syafi'ul; Munir, Ahmad (TELL - US JOURNAL, 2024)
Since assessment is an essential component of education, various assessments, both short-term and long-term, can be used throughout or at the end of the learning process. Among these, alternative assessment becomes prominent to be applied. This study reveals the teachers’ views and experiences, the potential advantages, and challenges of implementing alternative assessment in primary international schools. Data were collected through open-ended questionnaire from international primary school teachers that have experienced more than 10 years. This study discovered four notable benefits and three notable challenges that have been deduced from the current theoretical framework. The benefits can be classified into four main categories: enhancing students' performance, catering to different learning styles and preferences, emphasizing process-oriented learning, and promoting motivation. The three obstacles are to the issues of subjectivity and trustworthiness, time limitations, and the selection of the suitable methodology. Alternative assessment is crucial as it offers a valuable opportunity to improve students' learning and should be implemented to allow students to strengthen their skills. Hence, it is imperative for EFL teachers to regard alternative assessment as a viable option for classroom assessment.